Rhizoglomus variabile and Nanoglomus plukenetiae, native to Peru, promote coffee growth in Western Amazonia - Corazon-Guivin, M.A.; Romero-Cachique, G.; Del Aguila, K.M.; Padilla-Dominguez, A.; Hernandez-Amasifuen, A.D.; Cerna-Mendoza, A.; Coyne, D.L.; Oehl, F. (MDPI, 2023)
Coffee (Coffea arabica) is among the world’s most economically important crops. Coffee was shown to be highly dependent on arbuscular mycorrhizal fungi (AMF) in traditionally managed coffee plantations in the tropics. The objective of this study was to assess AMF species richness in coffee plantations of four provinces in Perú, to isolate AMF isolates native to these provinces, and to test the effects of selected indigenous AMF strains on coffee growth. AMF species were identified by morphological tools on the genus level, and if possible further to the species level. Two native species, Rhizoglomus variabile and Nanoglomus plukenetiae, recently described from the Peruvian mountain ranges, were successfully cultured in the greenhouse on host plants. In two independent experiments, both species were assessed for their ability to colonize coffee seedlings and improve coffee growth over 135 days. A total of 35 AMF morphospecies were identified from 12 plantations. The two inoculated species effectively colonized coffee roots, which resulted in 3.0–8.6 times higher shoot, root and total biomass, when compared to the non-mycorrhizal controls. R. variabile was superior to N. plukenetiae in all measured parameters, increasing shoot, root, and total biomass dry weight by 4.7, 8.6 and 5.5 times, respectively. The dual inoculation of both species, however, did not further improve plant growth, when compared to single-species inoculations. The colonization of coffee by either R. variabile or N. plukenetiae strongly enhances coffee plant growth. R. variabile, in particular, offers enormous potential for improving coffee establishment and productivity. Assessment of further AMF species, including species from other AMF families should be considered for optimization of coffee growth promotion, both alone and in combination with R. variabile.